The Pro-tumorigenic IL-33 Involved in Antitumor Immunity: A Yin and Yang Cytokine - Fournié, Jean-Jacques; Poupot, Mary (Frontiers in Immunology, 2018)
Interleukin-33 (IL-33), considered as an alarmin released upon tissue stress or damage, is a member of the IL-1 family and binds the ST2 receptor. Firstly described as a potent initiator of type 2 immune responses through activating T helper 2 (TH2) cells and mast cells, IL-33 is now known as also an effective stimulator of TH1 immune cells, natural killer (NK) cells, iNKT cells and CD8 T lymphocytes. Beside, IL-33 was shown to have an important contribution to several cancers with pro and anti-tumorigenic functions. Actually, IL-33 is a possible inducer and prognostic marker of cancer development with a direct effect on tumor cells promoting tumorigenesis, proliferation, survival and metastasis. IL-33 also promotes tumor growth and metastasis by remodeling the tumor microenvironment (TME) and inducing angiogenesis. IL-33 favors tumor progression through the immune system by inducing macrophages M2 polarization and tumor infiltration, and upon activation of immunosuppressive cells such as myeloid-derived suppressor cells (MDSC) or regulatory T cells. Besides, the anti-tumor functions of IL-33 depends on the infiltrated immune cells too but displaying TH1 responses. Thus, the recently proposed harnessing of IL-33 for cancer immunotherapies should be considered with caution, owing to the dual roles of this cytokine in cancer summarized in this review.